S107 Explaining The Mortality Gap In Copd Patients After Myocardial Infarction: Data From The Uk Myocardial Ischaemia National Audit Project (minap). (10th November 2014) - Rothnie, KJ; Smeeth, L; Herrett, E; Pearce, N; Hemingway, H; Timmis, A; Wedzicha, J; Quint, JK
Abstract : Introduction: COPD patients are at increased risk of myocardial infarction (MI) and have increased mortality after an MI. Although some of this increased risk may be due to COPD itself, differences in management after an MI may play a role. 1 We therefore investigated whether the increased in-hospital and 180 day mortality for COPD patients could be explained by differences in in-hospital and discharge treatment. Methods: Patients with a first MI between 2003–2013 were identified from the UK MINAP database. COPD patients had a record of obstructive airway disease, smoking history and were aged >35 years. Logistic regression was used to compare mortality in-hospital and at 180 days post-discharge between COPD and non-COPD patients. All models were adjusted for age, sex, smoking, previous cardiovascular disease, renal failure, diabetes and cardiovascular drugs used on admission. Variables relating to in-hospital management (delay in diagnosis, use of reperfusion and time to reperfusion/use of angiography in-hospital) and use of secondary prevention on discharge were then sequentially added to models to assess the extent to which they explained the mortality difference. Results: 300, 146 patients with a first MI were identified. 34, 027 (11.3%) had COPD. In-hospital mortality was greater for COPD patients after a STEMI (see Table 1 ), this difference was reduced after adjusting for in-hospital factors. Mortality was also greater for COPD patients at 180 days; this was not reduced after adjustment for in-hospital factors, but was reduced after adjusting for use of secondary prevention. In-hospital mortality was also greater for COPD patients after a non-STEMI, this was reduced after adjusting for in-hospital factors. Mortality at 180-days after a non-STEMI was greater for COPD patients, this was reduced after adjusting for in-hospital factors, but not after adjusting for use of secondary prevention. Conclusions: Improved recognition and timely use of reperfusion treatments after a STEMI may significantly reduce the in-hospital mortality for COPD patients. Longer term mortality in COPD patients after a STEMI may be improved by increased use of secondary prevention drugs. Increased use of timely angiography may improve mortality for COPD patients after a non-STEMI. Reference: Quint, JK et al . BMJ . 2013;347:f6650